2011
DOI: 10.1002/jbm.a.33111
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Ag nanoparticles/FGF‐2 on a modified titanium implant surface and improved human gingival fibroblasts behavior

Abstract: The objective of this study was to form a rapid and firm soft tissue sealing around dental implants that resists bacterial invasion. We present a novel approach to modify Ti surface by immobilizing Ag nanoparticles/FGF-2 compound bioactive factors onto a titania nanotubular surface. The titanium samples were anodized to form vertically organized TiO(2) nanotube arrays and Ag nanoparticles were electrodeposited onto the nanotubular surface, on which FGF-2 was immobilized with repeated lyophilization. A uniform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
46
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 75 publications
(92 reference statements)
0
46
0
Order By: Relevance
“…Upon cell study with human gingival fibroblasts (HGFs), the modified surfaces enhanced HGF functions with negligible cytotoxicity (Fig. 10.11b) [149]. In another strategy aiming towards enhancing osseointegration, Lee et al loaded N-acetyl cysteine (NAC) in TNTs and investigated its effect on bone formation in vitro and in vivo [150].…”
Section: Tnts For Osseointegrationmentioning
confidence: 98%
See 3 more Smart Citations
“…Upon cell study with human gingival fibroblasts (HGFs), the modified surfaces enhanced HGF functions with negligible cytotoxicity (Fig. 10.11b) [149]. In another strategy aiming towards enhancing osseointegration, Lee et al loaded N-acetyl cysteine (NAC) in TNTs and investigated its effect on bone formation in vitro and in vivo [150].…”
Section: Tnts For Osseointegrationmentioning
confidence: 98%
“…Studies with the human hepatocarcinoma [149], and c concept for applying TNTs on Ti wires as tiny implants for brain therapy [57]. Reproduced with permission from [57,149,152] cell line suggested increased cellular uptake of DNR and enhanced anti-tumor efficiency. Also shown was photocatalytic growth inhibition of cancer cells.…”
Section: Anti-cancer Therapymentioning
confidence: 98%
See 2 more Smart Citations
“…HGFs were cultured on the Ag/FGF-2 immobilized TNTs for cytocompatibility determination. 119 The result indicated that Ag/FGF-2-decorated TNTs has an excellent cytocompatibility compared to pure Ti, and the immobilized FGF-2 could enhance HGF cell attachment and proliferation. Furthermore, Bhattarai et al examined the feasibility of chitosan-gold nanoparticles conjugated with plasmid DNA/c-myb (Ch-GNPs/c-myb)-coated Ti implants and inserted it into rat mandibles to determine its in vivo effect.…”
mentioning
confidence: 93%